Application of Gold Silica Nanocomposites in Electrochemical Biosensors: A Review - Salma Nur Zakiyyah; Diana Rakhmawaty Eddy; M. Lutfi Firdaus; Yeni Wahyuni Hartati (PendIPA Journal of Science Education, 2021)
Gold silica nanocomposite-based biosensors are performing well in sensor technology for biosensor development. Due to this biosensor has good selectivity, excellent conductivity, large surface area, efficient enhancement of electron transfer between enzymes and electrodes and good biocompatibility. Therefore, gold silica nanocomposite can be an ideal matrix for immobilization of biomolecules. This review describes the method of synthesizing gold silica nanocomposites and their characterization, interaction with biomolecules and application of gold silica nanocomposites in electrochemical biosensors.